2011
DOI: 10.4303/jnp/n110401
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Manifestations ofLeishmania spp.Infection

Abstract: When listing common clinical signs of the spectra of Leishmania-derived diseases, neurologic malfunctions are not commonly included. Despite this, there are multiple reported instances both in human and veterinary medicine where neurologic manifestations, whether central or peripheral, are described. In this review, we describe neurologic manifestations seen during infection with Leishmania spp. with some discussion of the implicit effect of inflammation on the blood brain barrier in both medical and veterinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…The ␤-amyloid peptide and brevican, both found in the brain, bound to all the stationary-phase promastigotes tested and to most procyclic promastigotes. The ability of Leishmania strains to interact with molecules specifically expressed in the brain might be related to reported instances of central or peripheral neurologic manifestations during Leishmania infection both in humans and in animals (51) and to the detection of amastigotes in the central nervous systems of Leishmania-infected hamsters (52). The presence of brain proteins in the interaction repertoire of Leishmania parasites might ease their interaction with the brain environment.…”
Section: Discussionmentioning
confidence: 99%
“…The ␤-amyloid peptide and brevican, both found in the brain, bound to all the stationary-phase promastigotes tested and to most procyclic promastigotes. The ability of Leishmania strains to interact with molecules specifically expressed in the brain might be related to reported instances of central or peripheral neurologic manifestations during Leishmania infection both in humans and in animals (51) and to the detection of amastigotes in the central nervous systems of Leishmania-infected hamsters (52). The presence of brain proteins in the interaction repertoire of Leishmania parasites might ease their interaction with the brain environment.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the L. major parasites managed to cross the immunological blood-brain barrier, which has only rarely been reported for this cutaneous strain with very low levels of parasites detected [63]. However, dissemination of parasites to the central nervous system (CNS) has been frequently observed in visceral Leishmaniasis in both humans and dogs [64][67]. It has been suggested that parasites arrive in the CNS via infected leukocytes [65] and/or disruption to the blood brain barrier caused by inflammation [67].…”
Section: Discussionmentioning
confidence: 99%
“…The trypanosome Leishmania amazonensis is another parasite that can live in the brain of vertebrates (including humans) and has been associated with behavioral changes in its host (Petersen and Greenlee, 2011;Maia et al, 2015). Recently a study found that experimentally infected mice consistently had several key cytokines (IFN-y, IL-1,4,6,10) down regulated, while tumor necrosis factor alpha (TNF-α) was upregulated in the prefrontal cortex (Portes et al, 2016).…”
Section: Immunological Host Manipulation Immunological Manipulation Omentioning
confidence: 99%
“…However, this idea appears conflicting, as much of the evidence for the neuroimmune hypothesis in vertebrates, comes from cerebral parasites (Hemachudha et al, 2002;Klein, 2003;Bentivoglio and Kristensson, 2007;Sciutto et al, 2007;Hamilton et al, 2008;Henriquez et al, 2009;Petersen and Greenlee, 2011;Holland and Hamilton, 2013;Portes et al, 2016). Logic suggests that a parasite already present in the brain of a host will not have to by-pass the brains defenses in order to manipulate host behavior.…”
Section: Immunological Host Manipulation Immunological Manipulation Omentioning
confidence: 99%